LÐÐ¢Ð• ONSET OF SLE IN MALES: A MISDIAGNOSED DISEASE - Janev, Olivera Gjeorgjieva; Karanfilovski, Vlatko; Krstikj, Ljubinka Damjanovska (Journal of Morphological Sciences; Vol 5 No 2 (2022): JMS, 2022)
Systemic lupus erythematosus (SLE) is an autoimmune disease characterized by the production of antibodies to components of the cell nucleus in association with a diverse array of clinical manifestations. When the immune system attacks its own tissues, it causes widespread inflammation and tissue damage in affected organs. It can affect the joints, skin, brain, lungs, kidneys, and blood vessels. The primary pathological findings in patients with SLE are those of inflammation, vasculitis, immune complex deposition, and vasculopathy. Late-onset SLE represents a specific subgroup of SLE and is often initially missed leading to a significant delay in diagnosis.  Elderly patients frequently present to hospital with nonspecific symptoms such as fatigue, recurrent fever of an unknown cause, weight loss, serositis (pleural and/or pericardial effusions), and acute kidney injury. We are describing a case of late onset SLE in a male patient that has been previously only syptomaticaly treated for the complications of the disease itself, whilst it took a longer period for physicians to think of SLE and make further investigations about it, because of the age and sex of the patient.  Keywords : systemic lupus erythematosus, male, late onset, pleural effusion, myocadritits.